Characterization of Welded Joints (MIG and SAW) on LDX 2101 Duplex SS. (2015) - Graziano, Ubertalli; Firrao, Donato; Taveri, Gianmarco
Abstract: LDX 2101 (21, 5%Cr, 5%Mn, 1, 5%Ni and 0, 3%Mo) duplex stainless steel 255x123 mm sheets, 10 mm thick, have been welded by using either MIG (Metal Inert Gas) or SAW (Submerged Arc Welding) processes with appropriate filler material. It has been performed, in base material (BM), heat affected zone (HAZ) and fusion zone (FZ), metallographic and micrographic characterization (WDS image mapping, EDS chemical analysis, image analysis), evaluation of mechanical and physical properties (Vickers micro-hardness, tensile and impact testing) followed by SEM analysis and observation of fracture profile. WDS mapping images evidence alloying elements partition between ferritic and austenitic phases in the different zone of the welded sheets. The mechanical properties are even guaranteed in case of welding process, while the resilience values evidenced scattered values, however always above 40 J. No peculiar differences have been detected between the two employed welding processes, i.e. MIG and SAW.